Target Specific Inhibition of Protein Tyrosine Kinase in Conjunction With Cancer and SARS-COV-2 by Olive Nutraceuticals - Ghosh, Arabinda; Mukerjee, Nobendu; Sharma, Bhavdeep; Pant, Anushree; Kishore Mohanta, Yugal; Jawarkar, Rahul D.; Bakal, Ravindrakumar L.; Terefe, Ermias Mergia; Batiha, Gaber El-Saber; Mostafa-Hedeab, Gomaa; Aref Albezrah, Nisreen Khalid; Dey, Abhijit; et al. (Frontiers in Pharmacology, 2022)
Graphical Abstract